Sesame (Sesamum indicum L.) Growth and Yield as Influenced by Preemergence Herbicides - W. J. Grichar; P. A. Dotray; D. R. Langham (International Journal of Agronomy)
Studies were conducted during the 2007 and 2008 growing seasons under weed-free conditions in South Texas and the High Plains region of Texas to evaluate preemergence herbicides for sesame tolerance. No reduction in sesame stand was noted with any herbicide at south Texas location; however, at the High Plains location, linuron at the 2X rate reduced stand counts 28 days after treatment (DAT) in 2007 and diuron reduced sesame stand 147 DAT in 2008 when compared with the untreated check. At the 1/2X rate all herbicides exhibited minimal stunting while at the 1X rate stunting was variable and varied between locations. At the 2X rate, all herbicides caused sesame stunting compared to the untreated check. No herbicide, with the exception of linuron at the 2X rate in 2008 at the High Plains location, reduced sesame yield when compared with the untreated check. Although some herbicide treatments resulted in sesame stunting, this did not result in any yield reductions and this can be attributed to the ability of the sesame plant to compensate for injury and/or reduced stands.